TUMOR NECROSIS FACTOR ALPA (TNF-Î±) LEVEL IN DENGUE FEVER (DF) PATIENS AND DENGUE HEMORRHAGIC FEVER (DHF) PATIENTS - Siskayani, Ayu Savitri (WMJ (Warmadewa Medical Journal), 2018)
Dengue virus infection is still one of the health problems in tropical and subtropical regions. In its pathogenesis, some cytokines play an important role in the natural and adaptive immune response to the severity of dengue virus infection. Replication of dengue virus that activates macrophages will release cytokines for tumor necrosis factor (TNF-Î±), interleukin-1 (IL-1) and interleukin-12 (IL-12). This study aims to determine whether there are differences in mean TNF-Î± levels in DD and DHF patients. This study was an analytic observational study using cross sectional design, where blood samples were taken from 27 people with DD and 27 people with DHF. Serum TNF-Î± levels were analyzed by ELISA and TNF-Î± levels were analyzed statistically by Mann-Whitney test. The results showed the mean TNF-Î± level in DD patients was 76.82 Â± 1.20 pg / mL and in DHF patients was 195.15 Â± 30.30 pg / mL. This mean differed significantly (p